2002
DOI: 10.1183/09031936.02.01762002
|View full text |Cite
|
Sign up to set email alerts
|

BMPR2 germline mutations in pulmonary hypertension associated with fenfluramine derivatives

Abstract: This study investigated whether patients developing pulmonary arterial hypertension (PAH) after exposure to the appetite suppressants fenfluramine and dexfenfluramine have mutations in the bone morphogenetic protein receptor 2 (BMPR2) gene, as reported in primary pulmonary hypertension.BMPR2 was examined for mutations in 33 unrelated patients with sporadic PAH, and in two sisters with PAH, all of whom had taken fenfluramine derivatives, as well as in 130 normal controls. The PAH patients also underwent cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(125 citation statements)
references
References 30 publications
7
116
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Remarkably few recurrent mutations have been identified, with most mutations "private" to independent kindreds. The nonsense mutation W16X would generate the earliest premature termination codon reported thus far and effectively represents a null allele, consistent with the proposal that haploinsufficiency of BMPRII forms the molecular basis of IPAH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10] Remarkably few recurrent mutations have been identified, with most mutations "private" to independent kindreds. The nonsense mutation W16X would generate the earliest premature termination codon reported thus far and effectively represents a null allele, consistent with the proposal that haploinsufficiency of BMPRII forms the molecular basis of IPAH.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 More than 50 disease-causing defects in the gene encoding the type II receptor BMPRII are currently reported, many of which have been identified in patients with no known family history of PAH because of the low penetrance of these mutations. [2][3][4][5][6][7][8][9][10] Significant questions remain regarding the mechanisms through which BMPR2 mutations lead to the development of PAH. Analysis of the impact of disease-causing BMPR2 mutations on TGF-␤ signaling has provided little insight into the clinical variability of PAH, particularly in terms of disease penetrance, response to treatment, or age of onset, which may vary significantly within families.…”
mentioning
confidence: 99%
“…21 Although tolazoline indeed partially decreased pulmonary vascular resistance in a proportion of patients, it has since been realized that PAH is rather a disease of pulmonary arteriolar remodeling, related to a series of abnormal signaling mechanisms, among which the angiopoietin1-BMPR2 system has been recently suggested to play a central role. 2,[22][23][24] However, sympathetic activation may participate in pulmonary arteriolar remodeling. The pulmonary circulation is richly endowed with sympathetic nerve endings, 25,26 which seem to play an important role in vascular growth and differentiation, 27 albeit by yet undefined mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unclear whether some BMPR2 mutations are more or less penetrant, it is of interest to note the remarkable contrast to the spectrum of mutation types in FPAH in 10 patients in whom PAH occurred in association with either congenital heart disease (n 5 6) [Roberts et al, 2004] or followed exposure (albeit for various time periods) to the anorexic agents fenfluramine or amfepramone, and in the absence of a family history. Both are recognized risk factors for the development of PAH [Humbert et al, 2002;Abramowicz et al, 2003]. Closer inspection revealed that these subjects harbored predominantly missense mutations.…”
Section: Genotype^phenotype Observations and Disease Gene Penetrancementioning
confidence: 99%
“…Extensive analyses of the BMPR2 coding region and intronexon boundaries have been conducted in patients with FPAH and IPAH from a wide range of ethnic groups, including Americans, Europeans, Japanese, Chinese, Israeli Jews, and Indians [Lane et al, 2000;Deng et al, 2000;Thomson et al, 2000;Machado et al, 2001Machado et al, , 2003Morrell et al, 2001;Trembath et al, 2001;Humbert et al, 2002;Rudarakanchana et al, 2002;Uehara et al, 2002;Abramowicz et al, 2003;Rindermann et al, 2003;Runo et al, 2003;Cahn et al, 2004;Jing et al, 2004;Koehler et al, 2004;Morisaki et al, 2004;Roberts et al, 2004;Sugiyama et al, 2004;Zhicheng et al, 2004;Cogan et al, 2005;Harrison et al, 2005]. Mutations have been detected in up to 70% of recognized familial PAH cases Morisaki et al, 2004] ( Aldred et al, 2006), whereas in IPAH the reported mutation detection rate ranges from 11% to 40% [Thomson et al, [Cogan et al, 2005] ( Aldred et al, 2006).…”
Section: Spectrum Of Bmpr2 Mutations In Pahmentioning
confidence: 99%